Aksiological dominants of modern Kazakh literature in the light of the «Mangelic el» idea (Eurasian Journal of Philology Science and Education, 2016)
The literature of independent Kazakhstan inherent characteristic of artistic and aesthetic searches that require attention of researchers. In this respect, the idea of « Mangilik el» serves as the fundamental basis, designed to determine the historical continuity and the general link between generations, which is no future either for the people or for the state. Motherland, life, freedom, traditions of their ancestors, family, nature, work, fame, work performed orienting function in the works of Kazakh authors, merging with the general in an orderly system of values. Writer Satimzhan Sanbaev has a unique talent for a holistic view of culture in terms of the theme of the Kazakh nomadic, expressed in terms of the history and life of the people. Of particular interest is the analysis of value orientations as a reflection of the priorities recognized as strategic goals in life and general philosophical orientation. A prospective study of the writer’s favorite aspect allows you to understand the complex spiritual determinants, which serve representation, knowledge, ideals, attitudes and emotions of his characters, which are the core values of the Kazakh people.
Keywords: kazakh literature; axiological dominants; idea; story; lyrics; author; language; vocabulary; artistic world; outlook.